Special Measures for Crime Unit Police Resort Kudus in Law Enforcement of Infringement Currency Crime - Danail Arifin; Maryanto Maryanto (Jurnal Daulat Hukum, 2019)
This study aims to 1) special crimes unit Efforts to combat the crime of counterfeiting currency in the police resort Kudus; 2) The implementation of the inhibiting factors against the crime of counterfeiting currency in police resort Kudus; 3) The solution in overcoming barriers to enforcement against the crime of counterfeiting currency  Police resort KudusThe results showed that Significantly, the circulation of counterfeit money in Kudus Regency has experienced a dramatic decline in the period 2016 to 2017. It certainly shows that the performance of the police improved and further strengthen the Police in achieving the common goal of protecting the public. Role in preventing the circulation of counterfeit money by providing guidance and counseling especially those of the general public and institutions engaged in financial cooperation with Bank Indonesia. For problems counseling time and place, it is determined from the results of the evaluation in areas that are found counterfeit money circulation. Factors hindering the implementation of the Crime Against Counterfeiting Currency Police resort Kudus Already a strong determination of the Kudus Police to combat the crime of counterfeit money in circulation to the brain from the source or the manufacturer and distributor of counterfeit money because the circulation of counterfeit money has been very disturbing society and causing huge losses for the society and the state.Keywords: Crime; Law Enforcement; Counterfeit Currency.